A comprehensive study of the phase diagram of KxNa1-xNbO3 - Baker, D; Thomas, P; Zhang, N; Glazer, A (2009)
The phase diagram of lead-free piezoelectric Kx Na1-x NbO3 has been studied, with particular focus on the proposed morphotropic phase boundaries, by powder and single crystal x-ray diffraction. The tilt system and cation displacement has been mapped out as a function of temperature and composition, highlighting changes in the oxygen octahedra at x=0.2 and x=0.4 at room temperature. The orthorhombic to monoclinic boundary at x=0.5 has been investigated, with a subtle change in the structure observed. The conclusion is that Kx Na1-x NbO3 does not display a morphotropic phase boundary comparable with that in lead zirconate titanate, and that the most significant structural change as a function of composition occurs at x=0.2 because of the change of the tilt system. © 2009 American Institute of Physics.